Respuesta :

The expression is:

[tex]\sqrt{\frac{x^{3}x^{8}}{x^{6}}}[/tex]

We will use following steps to simplify it:

Step 1:

Use product property of exponents:

[tex]x^{a}*x^{b}=x^{a+b}[/tex]

[tex]x^{3}*x^{8}=x^{8+3}[/tex]

[tex]x^{3}*x^{8}=x^{11}[/tex]

That gives us the expression:

[tex]\sqrt{\frac{x^{11}}{x^{6}}}[/tex]

Step 2:

Use division property of exponents:

[tex]\frac{x^{a}}{x^{b}}=x^{a-b}[/tex]

[tex]\frac{x^{11}}{x^{6}}=x^{11-6}[/tex]

[tex]\frac{x^{11}}{x^{6}}=x^{5}[/tex]

This simplifies the expression:

[tex]\sqrt{x^{5}}[/tex]

Step 3:

Writing the square root as power 1/2:

[tex]\sqrt{x^{5}}=x^{5*\frac{1}{2} }[/tex]

[tex]\sqrt{x^{5}}=x^{\frac{5}{2} }[/tex]

Answer:

The final simplified form in x^n form is :

[tex]x^{\frac{5}{2} }[/tex]